Effect of Bio-Coating Material Concentration of Rice Husk Extract (Oryza Sativa) and Damar Resin (Agathis Dammara) on Reducing Corrosion Rates in H2SO4 Solutions - Pramudita, Marta; Zayadi, Adi; Pitaloka, Evi Diah; Rochmat, Agus; Pitaloka, Alia Badra; Agustina, Sri (Chemical Engineering Department, Engineering Faculty, Universitas Sultan Ageng Tirtayasa, 2024)
Corrosion is one of the main problems in industry, especially in cooling systems, refinery units, pipelines, chemicals, oil and gas production units, boilers and water processing, paints, pigments, lubricants, and others. The use of inhibitors has been proven to reduce the rate of corrosion. Still, it is limited by long-term stability, so it is necessary to provide other protection for mild steel, namely coating the metal with a coating material. Coating is the process of covering base material to protect the material from corrosion and provide protection to the material. The silica contained in rice husk extract and damar resin has the potential to be good bio-coating. This research aims to determine the effect of damar resin concentration on the corrosion rate and corrosion rate efficiency. The method used in this research uses several methods, one of which is the weight loss method. The resin and silica sol obtained from ashing rice husks are mixed to form a homogeneous product. Metal samples that have been coated with bio-coating material are soaked in 1 M sulfuric acid solution, with varying resin concentrations of 25, 50, and 75 gr with immersion times of 1, 2, and 3 hours, and at temperatures of 30, 40, 60, and 80 °C, which was then tested for the capability of the bio-coating material. This research obtained the highest corrosion rate value of 0.8860 mmpy using a temperature of 80˚C and a immersion time of 3 hours, with a corrosion efficiency value of 62.96%. Meanwhile, the lowest corrosion rate was 0.2143 mmpy at a temperature of 30˚C and a immersion time of 1 hour, with a corrosion efficiency value of 85.71%.